Epidemiological Profile and Outcome of Pregnancy Associated Acute Kidney Injury - Amin, Md Ruhul; Hoque, Al Mirajun; Hussain, Md Maruf; Bhattacharyya, Partho Moni; Sardar, Md Amzad Hossain; Hasan, Md Aminul; Alam, Md Mahidul (TAJ: Journal of Teachers Association, 2023)
Background: In developing countries, pregnancy-associated acute kidney injury (PAAKI) is a significant cause of maternal and neonatal mortality and morbidity. A systematic evaluation is essential to understand its frequency and severity in our setting. Objectives: Primary aim of our study was to evaluate the epidemiological profile and outcome of patients with pregnancy-associated acute kidney injury. Patients and Methods: The study was conducted in the Department of Nephrology, Rajshahi medical college hospital, from January 2019 to March 2020. A total of 83 patients with pregnancy-associated acute kidney injury were evaluated. Patients who had a history of chronic kidney disease or were diagnosed as a case of chronic kidney disease were excluded from the study. Result: The mean age±SD was 25.39±5.90 years. The majority were <30 years of age (56.6%). Only 24.1% had completed regular antenatal checkups. Preeclamsic toxaemia was present in 10.8% of patients. 85.5% of delivery was performed at hospitals/ clinics, and 75.9% of delivery was done by cesarean section. Unskilled birth attendants did 9.7% of delivery. Anaemia was present in 41.0% of patients at presentation, and 67.5% received a blood transfusion. Maternal mortality was 32.5%, and neonatal mortality was 21.7%. Renal replacement therapy was given in 56 (67.5%) patients. Among them, 47 (83.9%) received hemodialysis. Common causes of pregnancy-associated acute kidney injury were found to be sepsis (77.1%), postpartum hemorrhage (41.0%), disseminated intravascular coagulation (21.7%), severe preeclampsia (16.9%), HELLP syndrome (2.4%) and transfusion reaction (7.2%). 31.4% of patients recovered completely, and 10.8% of patients developed chronic kidney disease. Conclusion: Providing good quality perinatal care is essential to reduce the frequency of pregnancy-associated acute kidney injury and maternal and neonatal mortality related to this. TAJ 2022; 36: No-1: 127-134